Observing non-Hermiticity induced chirality breaking in a synthetic Hall ladder - Rui Ye; Yanyan He; Guangzhen Li; Luojia Wang; Xiaoxiong Wu; Xin Qiao; Yuanlin Zheng; Liang Jin; Da-Wei Wang; Luqi Yuan; Xianfeng Chen (Light: Science & Applications)
Abstract Non-Hermitian topological photonics plays a key role in bridging topological matter with gain and loss engineering in optics. Here we report the experimental observation of the break of chiral currents in a Hall ladder from the non-Hermiticity by constructing synthetic frequency dimension in two rings, where currents on both legs of the ladder co-propagate in the same direction. The origin of such phenomena is resulted from the interplay between the effective magnetic flux and the on-site gain and loss. Such non-Hermitian co-propagating currents exhibit characteristics of unidirectional frequency conversion in both rings, and moreover, different from the counterpart in Hermitian systems, can provide a method to probe the signatures of the non-Hermitian skin effect from steady-state bulk dynamics. Our model is further extended to models including next-nearest-neighbor couplings, pointing to a way for observing the non-Hermitian signature with higher winding number, and provides a new control knob for light manipulation with the topological dissipation engineering.